2007
DOI: 10.1186/1471-2458-7-70
|View full text |Cite
|
Sign up to set email alerts
|

Hyperendemic pulmonary tuberculosis in peri-urban areas of Karachi, Pakistan

Abstract: BackgroundCurrently there are very limited empirical data available on the prevalence of pulmonary tuberculosis among residents of marginalized settings in Pakistan. This study assessed the prevalence of pulmonary tuberculosis through active case detection and evaluated predictors of pulmonary tuberculosis among residents of two peri-urban neighbourhoods of Karachi, Pakistan.MethodsA cross-sectional study was conducted in two peri-urban neighbourhoods from May 2002 to November 2002. Systematic sampling design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…12 The low-income population also suffers from overcrowding or malnutrition and therefore is predisposed to developing tuberculosis. 13 Perception of illness has been found to vary with cultural, ethnicity, education, family structure and socioeconomic difference. 14 Treatment of active tuberculosis requires prolonged therapy (at least 6 months) with multiple and potentially toxic drugs which can lead to adverse reactions in a significant number of patients.…”
Section: Tuberculosis (Tb) Is a Chronic Infectious Disease Causedmentioning
confidence: 99%
“…12 The low-income population also suffers from overcrowding or malnutrition and therefore is predisposed to developing tuberculosis. 13 Perception of illness has been found to vary with cultural, ethnicity, education, family structure and socioeconomic difference. 14 Treatment of active tuberculosis requires prolonged therapy (at least 6 months) with multiple and potentially toxic drugs which can lead to adverse reactions in a significant number of patients.…”
Section: Tuberculosis (Tb) Is a Chronic Infectious Disease Causedmentioning
confidence: 99%
“…Barriers to programmes such as Ribolola include the belief that a significant proportion of TB suspects may not be able to provide sputum at home. 17 We found that, with education, most individuals could produce sputum, and removing the requirement to attend clinic may help overcome the attrition of contacts.…”
mentioning
confidence: 99%
“…Several reports from different countries have shown that the household contacts (HCs) of patients with active pulmonary TB are at a much higher risk of infection, which ranges from 30 to 80%, depending on the intensity of TB disease transmission (1,2,5,16,24,33,40). Most of the newly infected contacts of patients with TB contain the infection and do not develop disease.…”
mentioning
confidence: 99%